Antimicrobial activity and pharmaceutical development of essential oil from Hyptis suaveolens - S. Okonogi (2018)
Volatile oil distilled from the overground part of Hyptis suaveolens was preliminary quality controlled by GC. The antibacterial activity of this volatile oil was tested against various kinds of bacteria and fungi that caused dermatological diseases by agar dilution method. It was found that the volatile oil from H. suaveolens inhibited certain bacteria and fungi. A number of cream bases were prepared and evaluated for the satisfactory physical properties and stability. The creams containing 30% w/w of oil in four selected bases were tested for their stability, antimicrobial activity and primary irritation test using Garamycin® cream (0.1% gentamicin) as a positive control. It was found that all formulations showed a moderate antibacterial activity. © ISHS 2005.